Single Nucleotide Polymorphism (SNP) Exon 4 Proclatine Gene on Local Duck - Rafian, Teguh; Yurnalis, Yurnalis; Husmaini, Husmaini; Arlina, Firda (Jurnal Sain Peternakan Indonesia, 2024)
This study uses the sequencing method to determine the genetic diversity of the prolactin gene (PRL) in the exon four region in Bayang ducks. This study used 118 blood samples of Bayang ducks. Blood samples were isolated and then sequenced using a pair of primers L: 5'- GCA CAG TTG TTC TTA CTA GTT CG -3' and R: 5'- TCT GAG AAC TTT GCA GCT ATC T -3', which produced a 586 bp fragment in the Prolactin (PRL) gene exon 4. The amplification product was sequenced using First Base Singapore's services. The results showed that there were 16 polymorphisms in the exon four region and parts of introns 3 and 4 in the Bayang duck sample, namely two deletions at position -223C>del and -218A>del and 14 mutations at position -136G>A, 157G>A, +9T>G, +11G>A, +16T>C, +20A>C, +25T>C, +29A>C, +35T>A, +38A>G, +43C>A, +71G>A, +84G>A, +91T>A. Based on the study results, it can be concluded that the diversity of the prolactin gene (PRL) of Bayang ducks in the exon four region is polymorphic and can be used as a candidate for marker-assisted selection in Bayang ducks.